Sistem Telemetri Akusisi Data Injeksi Plastik Menggunakan Xbee Pro S2C - Irwanto Zarma Putra; Yopie Manurung; Illa Aryeni; Vivin Octowinandi; Erita Astrid; Citra Dewi; Ricky Maulana (Journal of Applied Electrical Engineering, 2023)
Plastic injection machine is a plastic product making machine with an injection molding process. Plastic injection machines at PT Shimano Batam currently cannot be monitored automatically. Therefore, a system is needed that monitors and stores all data about the performance of the plastic injection machine automatically. In this system Arduino Uno is used as a microcontroller of the plastic injection machine signal and the Xbee Pro S2C module is used as a sender and receiver of data packets from the plastic injection machine, the data is processed and then displayed on a PC and stored on the server. The test results of this system show that the machine status data matches the data displayed on the PC. From the results of testing the engine cycle time as much as 11 times, there is the largest difference in processing time, which is 1.20 seconds. From the results of reliability testing, packet loss was obtained by 0.006%. Xbee Pro S2C communication testing with a distance of 1 meter to 60 meters was successful without any data packets lost, when testing Xbee Pro S2C communication with a distance of 85 meters to 110 meters there were 30 data packets lost.